2012
DOI: 10.1021/cm300539a
|View full text |Cite
|
Sign up to set email alerts
|

Conformal Formation of (GeTe2)(1–x)(Sb2Te3)x Layers by Atomic Layer Deposition for Nanoscale Phase Change Memories

Abstract: Phase change random access memory appears to be the strongest candidate for next-generation high density nonvolatile memory. The fabrication of ultrahigh density phase change memory (≫1 Gb) depends heavily on the thin film growth technique for the phase changing chalcogenide material, most typically containing Ge, Sb and Te (Ge–Sb–Te). Atomic layer deposition (ALD) at low temperatures is the most preferred growth method for depositing such complex materials over surfaces possessing extreme topology. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
73
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(87 citation statements)
references
References 20 publications
(32 reference statements)
14
73
0
Order By: Relevance
“…28). The injection/purge times for the precursors of Sb(OC 2 H 5 ) 3 and 3[(CH 3 ) 3 Si] 2 Te were 0.75 s/9 s and 0.1 s/9 s, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…28). The injection/purge times for the precursors of Sb(OC 2 H 5 ) 3 and 3[(CH 3 ) 3 Si] 2 Te were 0.75 s/9 s and 0.1 s/9 s, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, it has been reported that a trench structure cell of high aspect ratio has a heat confinement effect to reduce thermal energy loss and cross talk between adjacent cells in the phase transition process [8,9]. Deposition has also moved from conventional physical vapor deposition (PVD), such as sputtering and evaporation, to chemical vapor deposition (CVD) and atomic layer deposition (ALD) [10,11]. However, deposition inside the trench cell without any voids is difficult even by CVD, and, up to now, ALD is the only viable solution for fine step coverage and surface roughness control.…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al reported the selective growth of stoichiometric GeSbTe on the TiN plug material in a contact hole formed in a SiO 2 dielectric layer by using multiple precursors23. Eom et al demonstrated the selective deposition of (GeTe 2 ) (1−x) (Sb 2 Te 3 ) x into 120 nm diameter pores by atomic layer deposition24. Position-controlled synthesis of single-crystal chalcogenides nanoplate arrays on mica substrates has also been reported using van der Waals epitaxy2526.…”
mentioning
confidence: 99%